The Effect of BAP and IBA on In Vitro Root Cultures of Acehnese Pomelo (Citrus maxima (Burm.) Merr.) - Handayani, Ira; Nazirah, Laila; Handayani, Rd. Selvy (Journal of Tropical Horticulture, 2020)
Acehnese pomelo is considered as a potential fruit to be developed for its economic and nutritional values. However, there is a main problem in developing this fruit. Pomelo sometimes is grown from seeds, but nowadays the fruits are often found to be having lesser seeds or even seedless. Besides, it is quite challenging to grow this local pomelo not only due to the scarce of the seeds, but it also cannot be conventionally germinated. Therefore, we need to develop this fruit through tissue culture. The purpose of this study was to investigate the effect of growth regulators on germination of pomelo seeds in vitro and its organ formation from in vitro root explants seed-originated of pomelo. The study was conducted at Plant Tissue Culture Laboratory, Faculty of Agriculture, Malikussaleh University. In October 2018 to April 2019. The research was divided into two separate experiments: 1) in vitro germination of pomelo seeds and 2) in vitro organ formation from root explants from of pomelo seeds. The first experiment using Complete Randomized Design (CRD) with 10 replications. The only factor observed was the use of BAP (0 and 2 mg/l). The second experiment was the examination of plant organ formation from root explants of pomelo seeds. This experiment had 2 factors observed. The first factor was different concentrations of BAP (0, 1, and 2 mg/l). The second factor was the different concentration of IBA (0, 1.25, and 2.5 mg/l). The results indicated that the application of BAP influenced the germination of pomelo seeds. The application of 2 mg/l BAP attributed to slower growth of shoots and roots, but it demonstrated better number of shoots, roots and leaves compared to application of 0 mg/l BAP. Pamelo root explants can form adventitious shoots on media eventhough without growth regulator (BAP 0 mg/l + IBA 0 mg/l), but optimization still needs to be done in order to obtain the best concentration to initiate shoot formation.